Penggunaan AI Berbasis Large Language Models (LLM) sebagai Media Interaktif dalam Pendidikan Bahasa dan Hukum di Perguruan Tinggi - Sylvia, Rena (Disiplin : Majalah Civitas Akademika Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2025)
The development of Artificial Intelligence (AI) technology has brought significant transformation to the field of education, including language and law. One of the most prominent innovations in AI is the emergence of Large Language Models (LLMs) such as ChatGPT, GPT-4, and BERT, which are capable of understanding and generating contextual text similar to human communication. This article aims to analyze the role of LLMs as interactive media in language and law education at the university level, as well as to examine the accompanying challenges and ethical implications. The findings indicate that LLMs hold great potential in enhancing critical thinking skills, understanding of legal language, and active student engagement through AI-based dialogue. However, their implementation also faces risks such as diminished originality, algorithmic bias, technological dependency, and privacy violations. Therefore, the role of lecturers is crucial as ethical facilitators, knowledge curators, and guides of humanistic learning. With the right approach, the integration of LLMs can foster an adaptive, interactive, and ethically grounded education that promotes critical intelligence and academic integrity in the digital era.